THE EFFECTS OF PERMEABILITY ANISOTROPY ON RESERVOIR ROCK TYPING USING DIGITAL ROCK PHYSICS METHOD - Fakhri Athallah, Muhammad
Rock typing is an essential process for characterizing and describing reservoirs in various engineering applications. However, the presence of rock permeability anisotropy can complicate this process. Anisotropic permeability can have a significant impact on fluid flow and transport within the material, with horizontal maximum permeability (kx), horizontal 90 degrees permeability (ky), and vertical permeability (kz) being the key parameters. The Direct Reservoir Parameterization Digital Rock Physics (DRP) method allows for faster calculation of anisotropic permeability values. CT-scan core data from a study on Bentheimer Sandstone was processed using DRP software to obtain porosity and anisotropic permeability values. Subsequently, the Hydraulic Flow Unit (HFU), Global Hydraulic Element (GHE), Winland, and Irawan Method techniques were employed to classify rock typings. Based on the research findings, it was discovered that the anisotropic permeability values in each direction (x, y, and z) yielded different rock typing results when using the HFU, GHE, and Winland methods, which should ideally produce the same results since they originate from the same rock. However, these results differed when the Irawan Method technique was applied (Irawan et al., 2019). The 25 samples of Bentheimer Sandstone showed consistent rock typing across all three axes (x, y, and z), providing evidence that the Irawan Method technique can accommodate permeability anisotropy. Additionally, the DRP method was considered more efficient in determining porosity and permeability values compared to conventional laboratory methods, which require more time and cost. Therefore, it can be concluded that the DRP method has significant potential in determining crucial parameters for reservoir characterization.